Nitrogen Removal in Textile Wastewater Using Combined Anaerobic-Aerobic System - Adam, Aofah (2004)
The objective of this study is to determine the percentage of nitrogen removal in textile wastewater effluent using combined anaerobic-aerobic system. The raw wastewater was of COD concentration between 385 to 1500 ppm at normal operating conditions. The anaerobic reactor has a capacity of 18 liters; meanwhile the aerobic reactor has a capacity of 9 liters to cater for a flow rate of 18 liters/day. Concentration of biomass was achieved through entrapment in the macrostructure of Cosmo (HDPE) balls used in the anaerobic reactor. The hydraulic retention time (HRT) for the anaerobic reactors was controlled at 24, 18, 12 and 8 hours. The Cosmo balls used in the system had proven to be an effective carrier material, which functioned as a separation device, thus limiting biomass being washed out. The maximum removal of ammoniacal nitrogen, BOD, COD and VSS for the Selangor Cotton Sdn Bhd textile wastewater were 84.62%, 63.64%, 60% and 98.9% respectively. Levels in the final effluent for ammoniacal nitrogen, BOD, and COD were recorded at 1.11 mg/l, 13.17 mg/l and 108.75 mg/l respectively. Kinetic parameters for nitrification using the anaerobic-aerobic reactor were found to be YN= 0.2305 mgVSS/mgNH4, Kd = 0.1987 day -1, Am = 1.196 day -1, KN= 4.302 mg/l. Meanwhile the kinetic parameters for denitrification using the anaerobic-aerobic reactor were: YD= 0.0025 mgVSS/mgNO3, Kd= 0.0026 day -1, Am = 0.00543 day -1, KD = 18.514mg/l.